Innovation and Adaptation of Indonesian SMEs in Facing Global Market Competition - Asmar Asmar; Nurul Emil Safitri; Mukarramah Syukur; Adriansyah Adriansyah (Pinisi Business Administration Review, 2026)
This study explores how Indonesian small and medium enterprises (SMEs) interpret and implement innovation and adaptation in facing global market competition. Using a qualitative research design, the study involved fifteen SMEs in the Jakarta Metropolitan Area representing manufacturing, creative, service, and digital sectors. Data were collected through semi-structured interviews, document analysis, and field observations. The data were analyzed using thematic analysis through coding, theme development, and interpretation based on the research questions. The findings show that innovation among Indonesian SMEs tends to be incremental, practical, and context-driven rather than based on formal research and development. SMEs adapt by modifying products, improving business processes, using digital platforms, strengthening networks, and responding to changing consumer preferences and supply chain pressures. Sectoral characteristics influence the form of innovation, with digital and service SMEs adopting technology-based solutions, while manufacturing SMEs focus on design adjustment, local sourcing, and collaboration. Internal factors such as leadership orientation, learning capacity, and decision-making flexibility shape the speed and quality of adaptation. External factors, including market competition, government support, and digital ecosystem initiatives, also influence SME competitiveness. The study concludes that innovation and adaptation in Indonesian SMEs are continuous, dynamic, and embedded in daily business practices. These findings provide practical insights for SME owners, policymakers, and business advisors in strengthening competitiveness through capacity building, digital integration, and context-sensitive support.